Next-generation Sequencing of an Ovarian Spindle Cell Tumor Identified an Ovarian Low-grade Endometrial Stromal Sarcoma: A Rare Entity. (September 2019) - Choi, Youn Jin; Ho, Jungyoon; Yoo, Jigeun; Liu, Jingjing; Lee, Ahwon; Park, Jong Sup; Hur, Soo Young
Abstract : Ovarian spindle cell tumors comprise a heterogeneous group of ovarian neoplasms from benign to malignant. Since this morphologic finding describes a broad category of ovarian neoplasms, it is not easy to determine an accurate diagnosis. Low-grade endometrial stromal sarcoma (LG-ESS) is a rare gynecological malignancy that presents with spindle cell lesions. To identify ovarian LG-ESS, we performed whole-exome sequencing and transcriptome sequencing of a spindle cell tumor. The tumor harbored JAZF1-SUZ12, a well-known gene fusion commonly found in uterine LG-ESS. Moreover, 28 non-silent somatic mutations (13 frameshift, 12 missense, 2 nonsense and 1 splicing mutations) with five cancer-related genes ( ACSL3, ATM, DST, HGF and PKHD1 ) were detected. Our results indicate that next-generation sequencing combined with conventional immunohistochemical analysis may be a better strategy than conventional analysis alone to identify ovarian LG-ESS with spindle cell lesions. Moreover, our data suggest that ovarian LG-ESS can harbor genetic characteristics similar to those of uterine LG-ESS. Abstract : Supplemental Digital Content is available in the text.